Topographical relation of parotid salivary gland to facial nerve in human fetuses - Butrymowicz, Bogdan (Anthropological Review, 1976)
On the basis of 19 fetuses in age 14-37 weeks examination the author has found that two lobec of parotid gland are more distinct in fetal period than after termination of intrauterine life.